2005
DOI: 10.1097/01.wnr.0000183898.47160.15
|View full text |Cite
|
Sign up to set email alerts
|

Neural responses to aggressive challenge correlate with behavior in nonbreeding sparrows

Abstract: The present study was conducted on captive male song sparrows (Melospiza melodia) during the nonbreeding season in order to 1) examine Fos and Zenk responses of basal forebrain sites to simulated territorial intrusion (STI), and 2) determine how those responses relate to aggression. Numerous forebrain areas showed significant Fos and Zenk responses to STI, and in several areas of the hypothalamus and lateral septum, these responses were negatively correlated with aggressive behavior. Homologous areas in mammal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 26 publications
2
65
0
Order By: Relevance
“…Once the area has been localized, templates are superimposed on digital images of the sections. We have extensively validated this method in other studies (including five species) by comparing our template positioning (onto sections that were labeled for immediate early genes) with the distribution of histochemical markers in adjacent sections (Goodson and Evans, 2004;Goodson et al, 2005a; also see Goodson et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the area has been localized, templates are superimposed on digital images of the sections. We have extensively validated this method in other studies (including five species) by comparing our template positioning (onto sections that were labeled for immediate early genes) with the distribution of histochemical markers in adjacent sections (Goodson and Evans, 2004;Goodson et al, 2005a; also see Goodson et al, 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in comparison to three gregarious species, the territorial violet-eared waxbill exhibits significantly greater responses within a discrete suite of forebrain areas -the ventrolateral LS, medial extended amygdala (nucleus taeniae and BSTm), AH and VMH. This suite of areas likely coordinates behavioral responses to aversive social stimuli (for discussion, see Goodson, 2005;Goodson et al, 2005b;also Sheehan et al, 2001). As in the present study, results for the modestly gregarious Angolan blue waxbill were virtually identical to the highly gregarious/colonial spice finch and zebra finch, with one exceptionthe medial extended amygdala, where an intermediate pattern of response was obtained (Goodson et al, 2005a).…”
Section: Neuropeptide Binding Densities and Evolution In Species-typimentioning
confidence: 99%
See 1 more Smart Citation
“…We quantitatively studied AR mRNA expression in the preoptic area (including different nuclei in the medial and lateral preoptic area), the BnST (bed nuclei of stria terminalis), the ventral pallidum, and the lateral septum. Previous research has shown that these nuclei contain androgen receptors and are involved in social, aggressive and copulatory behaviors [4,10,15,19,46,47] and might therefore represent nuclei that are possibly involved in early chick behavior.…”
Section: Introductionmentioning
confidence: 99%
“…8). For the year-round territorial song sparrow, immediate early gene results are largely comparable in winter and summer (4,5), although microarray data suggest that hypothalamic responses to simulated intrusion are very different in winter and summer, perhaps reflecting the fact that luteinizing hormone is released during territorial challenges only in the breeding season (9). Conversely, neurons that produce steroidogenic enzymes such as aromatase (ARO) may show greater activity in winter, given that territoriality in song sparrows shifts from reliance on gonadal steroids during the breeding season to nongonadal hormone production during the fall and winter (1,2).…”
mentioning
confidence: 99%